Activated microglia and neuroinflammation as a pathogenic mechanism in Leigh syndrome - Daneshgar, Nastaran; Leidinger, Mariah R.; Le, Stephanie; Hefti, Marco; Prigione, Alessandro; Dai, Dao-Fu (Frontiers in Neuroscience, 2023)
Neuroinflammation is one of the main mechanisms leading to neuronal death and dysfunction in neurodegenerative diseases. The role of microglia as primary mediators of inflammation is unclear in Leigh syndrome (LS) patients. This study aims to elucidate the role of microglia in LS progression by a detailed multipronged analysis of LS neuropathology, mouse and human induced pluripotent stem cell models of Leigh syndrome. We described brain pathology in three cases of Leigh syndrome and performed immunohistochemical staining of autopsy brain of LS patients. We used Ndufs4-/- mouse to study the effect of microglial partial ablation using pharmacologic approach. Human induced pluripotent stem cell-derived neurons and brain organoid with Ndufs4 mutation were used to investigate the neuroinflammation in LS. We reported a novel observation of marked increase of Iba-1 cells with features of activated microglia, in various parts of brain in postmortem neuropathological examinations of 3 Leigh syndrome patients. Using Ndufs4-/- mouse model for Leigh Syndrome, we showed that depletion of microglia by Pexidartinib initiated at the symptom onset improved neurological function and significantly extended lifespan. Ndufs4 mutant LS brain organoid had elevated NLRP3 and IL6 pro-inflammatory pathways. Ndufs4-mutant LS iPSC neurons were more susceptible to glutamate excitotoxicity, which was further potentiated by IL-6. Our findings of LS human brain pathology, Ndufs4-deficient mouse and iPSC models of LS suggest a critical role of activated microglia in the progression of LS encephalopathy. This study suggests a potential clinical application of microglial inhibition and immunosuppression during the active phase of Leigh Syndrome.